A STUDY ON PERFORMANCE AND CONSEQUENCES OF GST REGARDING MANUFACTURING OF COIR IN MSMEs IN INDIA - M.Vinoth; Mathiraj, SP. (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, the MSMEs have gained growth in Coir Production. India is that the largest coir producer within the world accounting for more than 80 per cent of the entire world production of coir fibre. The coir sector in India is extremely diverse and involves households, co-operatives, NGOs, manufacturers and exporters. In this study analysis of Performance Regarding Manufacturing of Coir in MSMEs by analyzing their Production of coir, Exports of Coir, Growth in production of coir products, State wise trends of employment in coir industry, Schemes implemented by the Coir Board, Research and Development (R&D), Budgetary support to the Coir Board. The study endeavors to gauge the MSMEs working execution, productivity, liquidity and dissolvability, to demonstrate that the business is led in a judicious and ordinary way which boosts the investors to invest in the Micro Small Medium Enterprises.